Identifikasi Morfologi pada Ikan Sidat (Anguilla spp) di Perairan Sungai Bali Selatan - Letia Alda Fadilla; I Wayan Arthana; Ni Luh Ayu Gita Astriani; Gde Raka Angga Kartika (Environmental Research Center (PPLH) of Udayana University, 2022)
Identification is necessary to identify the identity of an organism. Fish can be identified morphologically, namely by recognizing physical characteristics and looking for differences in the fish. This research was carried out for 3 months, from sampling, laboratory activities, and data analysis, starting from January 2021 to March 2021. Sampling was taken universally, samples were obtained from fishermen in the coastal waters of South Bali who caught eels. Laboratory activities are carried out at Fisheries Laboratory, Udayana University. This study used a descriptive analysis method. The sampling technique used in this study was probability sampling with simple random sampling. The stages carried out in this study were divided into two stages, including (1) sampling and (2) identification of morphological characters. The eel samples were obtained based on morphological identification of physical observation, eels are known to have a mottled pattern with slightly rounded oval tails and long fins. The morphometric measurements also obtained the results of the pre-dorsal length (PDL) ratio of 27.98%, the head length (HL) ratio of 14.14%, the ano-dorsal length (AD) ratio of 18.79%, and the ratio of pre-anal length (PAL) of 46.54%. The morphologically and morphometrically identified eel samples were identified as Anguilla marmorata.